Effects of blood flow restriction in nervous conduction velocity - Mouro, Miguel Silva (2019)
Purpose: In the last two decades, low intensity blood flow restricted (LI BFR) exercise has been increasingly used by individuals focused in hypertrophy gains. The practice of this type of training not following the procedures advanced in the literature, and neglecting factors such as: cuff pressure, wideness and placement as well as time of blood flow restriction might cause nerve damage. There are reports of individuals feeling numbness in the extremity of their limbs after enduring exercise with blood flow restriction (BFR). Thus, we explored whether BFR might affect peripheral nerve integrity both at resting and exercise conditions. Methods: Thirteen healthy young male participants (age: 22.0 ± 1.7 years, height: 175.2 ± 3.9 cm, body mass: 68.4 ± 5.4 kg and body mass index: 22.3 ± 1.5 kg/m2) were included in this study. Participants visited the laboratory on two different occasions (BFR and LIBFR at 60% arterial occlusion pressure (AOP) vs BFR and LI BFR at 80% AOP). The latency and amplitude of the M-wave and H-reflex were evaluated at 3 different moments (before, during and after BFR) at resting and exercise conditions. The stimulation of the posterior tibial nerve was performed in the popliteal fossae and the response was recorded on the soleus muscle. Both waves were elicited at 30% Mmax. Results: Overall, BFR had no impact on changing the amplitude or latency of either waveform. The latency difference between the M and H wave was unaffected by each condition (60 or 80%) (p > 0.05). Similar findings were also obtained for the interaction between BFR and Li exercise. Concerning the amplitude of both waveforms M-wave/H-wave, BFR (either 60 or 80%) had no effect altering the absolute or relative values of this specific variable with or without exercise (p > 0.05). Conclusions: Performing BFR at 60 or 80% AOP, for a period slightly > 5 min does not exert a negative impact on peripheral nerve function (unchanged amplitude and latency of evoked potential). Thus, we provide preliminary evidence that peripheral nerve conduction is not altered by BFR during resting or exercise conditions. Therefore, from a neurological standpoint, LI BFR exercise may be regarded as a safe mode of resistance training within the general population.